Methods for pads thermophysical parameters assessment in terms of 4P Soldering Model - Plotog, I.; Mihailescu, B.; Pencea, I.; Branzei, M.; Svasta, P.; Cucu, T.; Tarcolea, M. (Proceedings of the 2011 34th International Spring Seminar on Electronics Technology (ISSE), 2011)
In the case of surface mount technology (SMT), the 4P Soldering Process [1, 2, 3] concept defines solder joints as result of synergistic interactions and of correlation of Pad-Paste-Pin-Process considered as Key Process Input Variables (KPIV). As consequence, the PCB can be considered as a complex element defined in the design stage as a particular solution, function of finishing of the pad, geometry and substrate, having an unique set of thermophysical properties values. In the paper it will be presented the results of the research work done in order to develop new measurement methods of thermophysical properties of PCBs using a rework equipment, model PDR X410, as heat source and a infrared camera, type SC640 - FLIR SYSTEM, for quantification of PCB's surface temperatures. Thus, it results a practical solution for PCBs' thermo-physical properties measurement with application on assembling line. The implementation of this method in a soldering process will ensure solutions for improving the soldering parameters and to achieve the zero-defect production goal.